REPRESSION-DEPENDENT ALTERATION OF AN ARGININE ENZYME IN Escherichia coli - Leisinger, Thomas (1969)
Treatment of susceptible Escherichia coli K12 derivatives with 0.4 M Mg(++) at 37°, potentiated by L-arginine or L-canavanine, leads to alteration of acetylornithine δ-transaminase. The alteration, obtained in the absence of protein synthesis and reversible at 0 or 37°, is manifested in extracts by lowered activity and modified substrate affinity behavior of the enzyme without gross changes in sedimentation properties. Cells grown under arginine repression are susceptible to the treatment; cells grown under genetic or steady-state physiological derepression are not. Transaminase synthesized during early derepression can be altered, although to progressively diminishing extents. Enzyme formed under steady-state derepression becomes alterable following transition to repression. The Mg(++) -dependent alteration can be thought to arise while the enzyme, arginine (or canavanine), and aporepressor are in contact, and to reflect a physiological process such as the participation of the enzyme in the repressive complex.